2012
DOI: 10.3390/ijerph9093115
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Disaster Preparedness among Latino Migrant and Seasonal Farmworkers in Eastern North Carolina

Abstract: Natural disasters including hurricanes, floods, earthquakes, tornadoes, and fires often involve substantial physical and mental impacts on affected populations and thus are public health priorities. Limited research shows that vulnerable populations such as the low-income, socially isolated migrant and seasonal farmworkers (MSFW) are particularly susceptible to the effects of natural disasters. This research project assessed the awareness, perceived risk, and practices regarding disaster preparedness and respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 30 publications
2
47
1
1
Order By: Relevance
“…Our results challenge the literature suggesting that immigrants’ risk perception and disaster preparedness for natural disasters are different from their native‐born counterparts . Bourhis and colleagues posit that immigration and integration policies define the “social psychological reality” of how immigrants experience their lives in the receiving society.…”
Section: Discussioncontrasting
confidence: 88%
“…Our results challenge the literature suggesting that immigrants’ risk perception and disaster preparedness for natural disasters are different from their native‐born counterparts . Bourhis and colleagues posit that immigration and integration policies define the “social psychological reality” of how immigrants experience their lives in the receiving society.…”
Section: Discussioncontrasting
confidence: 88%
“…Familial modes of communication may target specific family members as entry points: for example, children who could be provided information at school. Improved disaster preparedness among foreign‐born Hispanics may also be achieved through deepened community engagement, more culturally competent approaches, participatory methods, as well as partnerships among universities, public health agencies, and community‐based organizations (Burke and others ). These community‐based approaches to disaster‐risk reduction may prove more effective for Hispanic immigrants and other socially vulnerable groups.…”
Section: Resultsmentioning
confidence: 99%
“…In a study of Florida single‐family homeowners, Walter Peacock found that Hispanic and black homeowners had lower levels of hurricane‐shutter usage than respondents from other racial/ethnic backgrounds, adjusting for income and other variables (2003). Racial/ethnic minorities may be less likely than non‐Hispanic whites to plan for emergencies or to feel prepared for emergencies (Burke and others ). For example, Sloane Burke and others found that Latino migrant farmworkers in North Carolina were highly underprepared for disaster (2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…While securing profitability for the agricultural sector, seasonal workers themselves are often caught in a cycle of poverty. Several studies have documented the transience and invisibility of underinsured or uninsured agricultural workers in a profession surrounded by occupational and environmental hazards (Burke et al, 2012;Winkelman et al, 2013). However, links to climatic hazards have not been explored.…”
Section: Introductionmentioning
confidence: 99%